Teaching the Subject of Repetitive Algorithms Based on Multimedia Electronic Manuals (Eurasian Journal of Learning and Academic Teaching, 2023)
The article discusses the method of mastering the subject of repetitive algorithms based on multimedia electronic manuals. In the teaching of this topic, it is intended to use multimedia tools to organize the lesson process and to show the process of explanation with the help of animation.